Dampak Sosial dari Perubahan Qaul Qadim Imam Syafii ke Qaul Jadid - Subli, Mohamad; Kurniati, Kurniati; Misbahuddin, Misbahuddin (PAPPASANG, 2023)
Abstract: The change in the law made by Imam Syafi'i in his ijtihad can have a social impact on social life. So the purpose of this study is to describe the social impact of the change in Imam Syafi'i qaul qadim to qaul jadid. The research method used in this study is the library research method, namely by examining sources from books and literature related to the formulation in this article. The research method used in this research is the library research method, namely by examining sources from books and literature related to the formulation in this article. the following are some conclusions that can be drawn by researchers: First, the history of the growth of the imam shafi'i school of thought is inseparable from the influence of his two teachers' schools, namely the school of imam malik and the school of imam abu hanifah. Second: The factors that influence the change in ijtihad in the school of Imam Shafi'i from qaul qadim to qaul jadid include: The existence of new Prophetic traditions or atsar found by Imam Shafi'i, the existence of arguments that are stronger (arjah) than previous arguments and the geographical differences between the two countries of Iraq and Egypt. Third; The social consequences of the change from qaul qadim imam shafi'i to qaul jadid can affect social relations in society, both Iraqi society and Egyptian society at that time, this is inseparable where both countries need to adjust to the new opinion of imam shafi'i. Abstrak: Berubahnya hukum yang dilakukan oleh Imam Syafi'i dalam ijtihadnya dapat memberikan dampak sosial bagi kehidupan bermasyarakat. sehingga tujuan dari penelitian ini adalah untuk mendeskripsikan dampak sosial dari perubahan qaul qadim Imam Syafi'i menjadi qaul jadid. Adapun metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kepustakaan (library research), yaitu dengan menelaah sumber-sumber dari buku-buku dan literatur-literatur yang berkaitan dengan rumusan dalam artikel ini. berikut ini beberapa kesimpulan yang dapat diambil oleh peneliti: Pertama; sejarah pertumbuhan mazhab imam syafi'i tidak terlepas dari pengaruh dua mazhab gurunya yaitu mazhab imam malik dan mazhab imam abu hanifah. Kedua: Adapun faktor-faktor yang mempengaruhi perubahan ijtihad dalam mazhab imam syafi'i dari qaul qadim menjadi qaul jadid, diantaranya: Keberadaan hadis-hadis Nabi atau atsar baru yang ditemukan oleh imam syafi'i, adanya dalil-dalil yang lebih kuat (arjah) dari dalil-dalil sebelumnya dan adanya perbedaan geografis antara kedua negara Irak dan Mesir. Ketiga; Akibat sosial dari perubahan qaul qadim imam syafi'i ke qaul jadid dapat mempengaruhi hubungan sosial dalam masyarakat, baik masyarakat Irak maupun masyarakat Mesir waktu itu, hal ini tidak terlepas dimana kedua negara tersebut perlu penyesuain terhadap pendapat baru imam syafi'i.